mean = (63 + 54 + 62 + 59 + 52)/5mean=63+54+62+59+525
mean = 58mean=58
n = 5n=5
63
x - mean = 63 - 58 = 5x−mean=63−58=5
(x - mean)^2 = 5^2 = 25(x−mean)2=52=25
54
x - mean = 54 - 58 = -4x−mean=54−58=−4
(x - mean)^2 = (-4)^2 = 16(x−mean)2=(−4)2=16
62
x - mean = 62 - 58 = 4x−mean=62−58=4
(x - mean)^2 = 4^2 = 16(x−mean)2=42=16
59
x - mean = 59 - 58 = 1x−mean=59−58=1
(x - mean)^2 = 1^2 = 1(x−mean)2=12=1
52
x - mean = 52 - 58 = -6x−mean=52−58=−6
(x - mean)^2 = (-6)^2 = 36(x−mean)2=(−6)2=36
Sigma(x - mean)^2 = 25 + 16 + 16 + 1 + 36 = 94
sigma^2 = (Sigma(x - mean)^2)/n = 94/5 = 18.8